Assessment and monitoring of Achilles tendinopathy in clinical practice: a qualitative descriptive exploration of the barriers clinicians face. Issue 2 (21st June 2022) - Murphy, Myles Calder; Debenham, James; Bulsara, Caroline; Chivers, Paola; Rio, Ebonie Kendra; Docking, Sean; Travers, Mervyn; Gibson, William
Abstract : Our primary objective was to explore the barriers preventing clinicians from implementing what they think is ideal practice as it relates to using tools to aid diagnosis and monitor progress in mid-portion Achilles tendinopathy. Our secondary objectives were to describe the assessments employed by clinicians in their own practice to aid with (a) diagnosis and (b) monitoring progress in Achilles tendinopathy and explore the outcome measure domains clinicians believe to be the most and least important when managing patients with Achilles tendinopathy. We employed a qualitative descriptive study design. Thirteen participants (eight female, five male) from across Australia, consisting of two junior physiotherapists, five senior physiotherapists working in private practice, four senior physiotherapists working within elite sports organisations and two sport and exercise medicine doctors, were included and one-on-one interviews were performed. Audio was transcribed then entered into NVivo for coding and analysis. Four main themes were perceived as barriers to implementing ideal practice of assessment and monitoring in people with Achilles tendinopathy: financial constraints, time constraints, access to equipment and patient symptom severity. Assessments related to function, pain on loading, pain over a specified time frame and palpation are commonly used to assist diagnosis. Assessments related to disability, pain on loading, pain over a specified time frame and physical function capacity are used to monitor progress over time. Furthermore, pain on loading and pain over a specified time frame were considered the most important outcome measure domains for assisting diagnosis whereas pain on loading, patient rating of the condition and physical function capacity were the most important outcome measure domains for monitoring progress. A number of barriers exist that prevent clinicians from implementing what they view as ideal assessment and monitoring for Achilles tendinopathy. These barriers should be considered when developing new assessments and in clinical practice recommendations.